2021
DOI: 10.1177/17085381211025168
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of endovascular versus open repair for ruptured abdominal aortic aneurysm – Meta-analysis of propensity score-matched data

Abstract: Background Optimal management of ruptured abdominal aortic aneurysms (rAAA) has been heavily debated in the literature. The aim of this review is to assess comparative outcomes from propensity-matched studies of endovascular versus open for rAAA. Methods Electronic databases (MEDLINE and Embase) were searched in January 2021 using the Healthcare Databases Advanced Search interface. Eligible studies compared endovascular versus open repair for rAAA using propensity-matched cohorts. Pooled estimates of periopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Of note, the early survival advantage of EVAR vs. OR may be pronounced in haemodynamically unstable rAAA patients [14]. A more recent meta-analysis that included almost 7000 patients reported similar findings, with a lower perioperative mortality after EVAR, although the hazard of overall mortality during follow-up was lower [15].…”
Section: Discussionmentioning
confidence: 75%
“…Of note, the early survival advantage of EVAR vs. OR may be pronounced in haemodynamically unstable rAAA patients [14]. A more recent meta-analysis that included almost 7000 patients reported similar findings, with a lower perioperative mortality after EVAR, although the hazard of overall mortality during follow-up was lower [15].…”
Section: Discussionmentioning
confidence: 75%
“…The literature has shown that patients with an rAAA who undergo EVAR have shorter hospital and ICU stays compared with open repair, and our data demonstrated a similar trend. 13,[40][41][42][43][44] However, both hospital and ICU length of stay increased overall for the postprotocol population. Although we anticipated the length of hospital stay and length of ICU stay to decrease after the introduction of the emergency EVAR protocol, 45 this finding may reflect increased instability and comorbidity of patients in the postprotocol period.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular management of ruptured AAA have demonstrated improved outcomes during last decade, showing that early mortality in ruptured AAA cases is estimated at 20% ( 34 36 ). Compared to standard endovascular repair for ruptured AAA and taking into consideration that 45% of patients in the current study were managed for extensive type I–III TAAAs, the early mortality could be considered acceptable both for urgent and emergent repair.…”
Section: Discussionmentioning
confidence: 99%